A kinematic analysis of the lower limb with regard to restricted spinal motion during gait - Song, Hyeon-Nam; Kim, Kyoung; Kim, Young Mi (Journal of Physical Therapy Science, 2017)
[Purpose] The purpose of this study was to investigate the effect of restricted spinal motion on kinematic changes in the lower extremities using a rigid thoracolumbosacral orthosis. [Subjects and Methods] Forty healthy males in their 20s were selected as the sample, which was randomly and evenly divided into two groups: (1) the WT group (with a thoracolumbosacral orthosis) and (2) the WOT group (without a thoracolumbosacral orthosis). The spinal orthosis used in this study was a thoracolumbosacral orthosis called a plastic body jacket. [Results] The sagittal plane; in the level ground walking measurements, significance differences were found at the H2 (Hip maximum flexion/extension in midstance phase) and K2 (Knee maximum flexion/extension in midstance phase) between the WT group and the WOT group. [Conclusion] It can be concluded that a spinal orthosis is useful in stabilizing the lower extremities during stair gaiting, and that appropriate application of the orthosis plays a supporting role in the activities of daily life and therapeutic intervention.